Analisis Kemampuan Reversibilitas Siswa MTs Kelas VII dalam Menyusun Persamaan Linier - Balingga, Epi; Prahmana, Rully Charitas Indra; Murniati, Novi (JURNAL REVIEW PEMBELAJARAN MATEMATIKA, 2016)
This study aims to determine the reversibility ability of the seventh-grade students in making the linear equations. This ability is known after all students complete ten questions given and some students selected to be interviewed. Instrument test findings, in the form of 10 questions reversibility capability that has valid and reliable. The subjects were 29 students of class VIII 1 in MTS Negeri Pagedangan in the academic year 2015/2016. Interviews conducted to see students ability to create a linear equation.As a result, most of the students have had the reversibility ability and the biggest difficulties of students in making similarity equation when its variable in the middle of the equation.Â